OC-06 - Pro-thrombotic biomarkers in pancreatic diseases: are they specific of cancer?. Issue 140 (April 2016) - Faille, D.; Ajzenberg, N.; de Chaisemartin, L.; Granger, V.; Chollet-Martin, S.; de Raucourt, E.; Hammel, P.; Lévy, P.; Ruszniewski, P.; Rebours, V.
Abstract : Introduction: Venous thrombo-embolic events (VTE) occur frequently in patients with pancreatic cancer and contribute to elevated morbidity and mortality. Clinical risk factors for thrombosis such as cancer stage and tumor grade have been clearly identified. Recently, several biomarkers have been proposed which may help identifying cancer patients at high risk of thrombosis. Those biomarkers have been studied in heterogeneous cohorts of patients with different cancer types. Aim: To compare pro-thrombotic biomarkers in pancreatic cancer and in chronic pancreatitis to determine whether these biomarkers are related to cancer or inflammation and to validate their association with thrombotic risk in a pancreatic cancer population. Materials and Methods: 45 patients with pancreatic cancer, 49 with intraductal papillary mucinous tumor of the pancreas (IPMN), a precancerous lesion, and 50 with chronic pancreatitis were recruited. Plasma levels of factor VIII, D-dimers, thrombin-antithrombin complexes, soluble p-selectin, tissue factor-dependent procoagulant activity of MP (TF-MP), free Tissue Factor Pathway Inhibitor (TFPI) and extracellular DNA were measured. Thrombin generation triggered by 1pM of TF was evaluated with the Calibrated Automated Thrombogram assay. Results: Levels of factor VIII, D-dimers, TF-MP, TFPI and extracellular DNA were significantly higher in cancer patients compared to IPMN or chronic pancreatitis (Table 1). Patients with metastatic cancer (n = 27) presented higher levels of D-dimers (mean ± sd 1.77 ± 1.28 vs 0.80 ± 0.96 μg/ml, p = 0.004) and MP-TF (54.3 ± 53.2 vs 15.8 ± 10.4 fM, p = 0.02) compared to patients with localized lesions (n = 18). Among cancer patients, 42 were followed for a median duration of 187 days (min 21-max 802 days). VTE occurred in 10 (23%) patients. All had metastatic cancer at the time of thrombosis. Only D-dimers were significantly elevated in cancer patients with VTE compared to patients without VTE (median 1.85 vs 0.7 μg/ml, p = 0.02). Table 1 Pancreatic cancer (n = 45) IPMN (n = 49) Chronic pancreatitis (n = 50) p-value Factor VIII (%) 197 ± 62 150 ± 43 146 ± 66 < 0.0001 D-dimers (μg/ml) 0.9 (0.22-4) 0.27 (0.22-3.07) 0.38 (0.17-4) < 0.0001 Thrombin-antithrombin (ng/ml) 3.9 (2-39) 3.2 (2-6.1) 3.6 (2.2-57)* 0.003 sP-selectin (ng/ml) 28 (6.5-157) 27 (8-63) 30 (4-67) 0.7 TF-MP (fM) 22 (0-198) 12 (0-51) 16 (0-66) 0.03 Free TFPI (ng/ml) 21 ± 12 12 ± 4 13 ± 7 < 0.0001 Extracellular DNA (ng/ml) 16.6 (0-408) 0 (0-193) 0 (0-197) < 0.0001 Thrombin peak (nM) 209 ± 59 240 ± 90 198 ± 80 0.02 Results presented as mean ± SD for data with Gaussian distribution or median (min-max) for skewed variables; p-value for one-way analysis of variance or Kruskal-Wallis test Conclusions: Elevation of factor VIII, D-dimers, TF-MP, TFPI and extracellular DNA seems to be related to cancer process, not to local or systemic inflammation as these parameters differentiate cancer from chronic pancreatitis. Interestingly, D-dimers and TF-MP are related to the disseminated cancer stage, suggesting that vascular invasion is a prerequisite to the release of TF-MP from the primary tumor into the bloodstream and to coagulation activation. However, only D-dimers are associated with the occurrence of future VTE. We propose that D-dimers could be a useful tool to predict thrombotic events in pancreatic cancer patients. This should be confirmed in a larger population.